Clinico-epidemiological profile of confirmed swine flu (H1N1) cases admitted at an infectious disease hospital in Kolkata, India - Sardar, Jadab Chandra; Sau, Arkaprabha; Mandal, Pankaj Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Swine flu is an acute infection of respiratory tract, caused by swine origin influenza A (H1N1) virus. Antigenic drift and shift of this virus is responsible for epidemic or pandemic in different parts of the world from time to time. Last pandemic started in 2009 at Mexico and USA, and spread globally with in a very short period of time. Post pandemic resurgence was noticed in various parts of India from 2010 to 2015. Methods: A record based descriptive study was carried out among the 89 confirmed swine flu (H1N1) cases admitted at Beliaghata ID and BG Hospital, Kolkata during last post pandemic resurgence in India between February 2015 to March 2015. Results: Among 89 confirmed swine flu cases 52.81% were male and 47.19% were female. Mean (±Standard Deviation) age was 38 (±18) yrs. Mean (±Standard Deviation) duration of hospital stay was 6.5 (±1.7) days. Among the admitted patients, 84 patients were discharged from the hospital but 5 patients succumbed to their illness. 95.51% patient presented with the chief complaint of fever. Among the admitted cases, 21.34% had either history of travel to swine flu (H1N1) infected area or contact with swine flu infected patients. There was a statistically significant association between outcome (death / discharge) and co-morbid conditions, (P value-0.047, α-5%, df-1). Conclusions: This study will help clinicians and public health specialist to understand the clinico-epidemiological profile of swine flu (H1N1) cases to diagnose, treat and to develop preventive strategies in future.